Comparative Study Of Financial Performance In Indonesian Mining Sector: Pre And During Covid-19 - Az Zuhri, Muhammad Rifky; Habiburrahman, Habiburrahman (LPPPIPublishing, 2024)
In early March 2020, Indonesia announced its first Covid-19 case, which led to a significant decline across various economic sectors. This study aims to analyze the financial performance of companies in the mining sector from 2019 to 2022, this research can assist companies in evaluating their financial performance and their competitors. It employs a quantitative method using two ratios: liquidity ratios utilizing indicators such as the quick ratio and current ratio, and profitability ratios including the Net profit margin ratio, Return on Assets (ROA), and Return on Equity (ROE). The research findings indicate that Covid-19 did have an impact, although not significant. There were observed variations in both decreases and increases in liquidity and profitability ratios among different companies.